2019
DOI: 10.1136/neurintsurg-2019-015519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of workflow metrics on clinical outcomes of low diffusion-weighted imaging Alberta Stroke Program Early Computed Tomography Score (DWI-ASPECTS) patients subjected to mechanical thrombectomy

Abstract: BackgroundAlthough accumulating evidence has demonstrated the benefit of mechanical thrombectomy (MT) in patients with low Alberta Stroke Program Early Computed Tomography Score (ASPECTS), it is still unclear how workflow metrics impact the clinical outcomes of this subgroup of patients.MethodsPatients with acute stroke and diffusion-weighted imaging (DWI) ASPECTS ≤5 at baseline, who underwent MT within 6 hours of symptoms onset, were included from a prospectively maintained national multicentric registry betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…After initial screening, we retrieved the full text of 68 records that were considered potentially eligible for inclusion, and after reading the full-text articles, 14 were further excluded (Supplemental eTable 2). Finally, we identified 24 eligible studies for inclusion, of which 1 was an individual patient data (IPD) meta-analysis of RCT-derived data conducted by the Highly Effective Reperfusion Using Multiple Endovascular Devices (HERMES) collaborators, 31 2 were RCTs not included in the previous meta-analysis, 32,33 16 were observational studies based on prospectively collected data (prospective registries), [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] and 5 were retrospective cohort studies (Table 1), [50][51][52][53][54] comprising a total of 2539 AIS patients with low ASPECTS score treated with EVT.…”
Section: Literature Search and Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…After initial screening, we retrieved the full text of 68 records that were considered potentially eligible for inclusion, and after reading the full-text articles, 14 were further excluded (Supplemental eTable 2). Finally, we identified 24 eligible studies for inclusion, of which 1 was an individual patient data (IPD) meta-analysis of RCT-derived data conducted by the Highly Effective Reperfusion Using Multiple Endovascular Devices (HERMES) collaborators, 31 2 were RCTs not included in the previous meta-analysis, 32,33 16 were observational studies based on prospectively collected data (prospective registries), [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] and 5 were retrospective cohort studies (Table 1), [50][51][52][53][54] comprising a total of 2539 AIS patients with low ASPECTS score treated with EVT.…”
Section: Literature Search and Included Studiesmentioning
confidence: 99%
“…The risk of bias in the included observational studies was assessed by the ROBINS-I tool and is presented in Supplemental eFigures 3-4. Overall, 16 studies were not controlled; 34,35,[37][38][39][40][41]43,45,46,48,49,[51][52][53][54] therefore, the assessment of confounding bias, bias in the classification of intervention, and bias due to deviations from intended interventions were not applicable. Yet, significant confounding bias was detected in all five controlled studies as there were several baseline differences between the patients' groups (EVTtreated versus BMT-treated).…”
Section: Quality Control Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multivariable analysis, voxel-based DWI reversibility >50%, but not volumetric DWI reversibility, was associated with outcome at 90 days. Previous studies found DWI reversibility to be associated with short- 14,15,18,20,22,28 and long-term outcome. 19–21,25,28 Since stroke lesions in our population were small, reversible lesion volumes were also not very large, potentially precluding an unambiguous effect on 90-day outcome.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, only 6% (n=225) of patients in the HERMES collaboration had low ASPECTS (≤5) making it difficult to draw any conclusions 4. In addition, a number of studies using registry data on patients with low ASPECTS have shown that older age, good collateral status, alteplase use, successful reperfusion, short onset to recanalization times, and baseline infarct volumes could potentially influence outcomes in these patients 5–9…”
Section: Introductionmentioning
confidence: 99%